0204 Food Insecurity is Associated with Objectively and Subjectively Measured Sleep. (12th April 2019) - Troxel, Wendy M; Haas, Ann; Ghosh-Dastidar, Bonnie; Richardson, Andrea; Buman, Matthew; Buysse, Daniel; Hale, Lauren; Kurka, Jonathan; Dubowitz, Tamara
Abstract: Introduction: Food insecurity (FI), defined as uncertainly about one's ability to access safe and nutritious foods due to financial constraints, is a profound source of stress and is associated with cardiometabolic risk. A few studies have shown that FI is associated with self-reported sleep. This is the first study to examine the association between FI and multiple dimensions of sleep, assessed objectively and subjectively. Methods: We examined data from predominantly African American adults (n= 785, mean age 56 (16.0) years; 77% female) living in low-income neighborhoods. FI was measured using a 10-item validated survey that assesses conditions and behaviors that characterize households lacking financial resources to meet basic food needs (over past 12 months). Sleep duration, efficiency, WASO, and variability in sleep duration were measured via wrist-worn actigraphy. Sleep quality was assessed via sleep diary. Analyses estimated each of the sleep outcomes as a function of FI, adjusting for individuals' sociodemographics and body mass index. We also tested psychological distress as potential mediator of observed associations. Results: Greater FI was associated with shorter actigraphy-assessed sleep duration (B=-2.44; SE=1.24, per 1-unit increase; i.e., 24 minutes shorter sleep for the most as compared to least insecure group) and poorer sleep efficiency (B=-.27; SE=.13); p's<.05), and poorer subjective sleep quality (B=-.03; SE=.01; p<.01). Greater FI was also associated with greater likelihood of short (< 7 hours; OR= 1.11; CI: 1.02-1.21) and long sleep (> 9 hours; OR =1.19; CI: 1.01-1.39), compared to the recommended sleep duration of 7-9 hours. There were no associations between FI and WASO or sleep variability. Psychological distress partially mediated the association between FI and subjective sleep quality. Conclusion: FI is an independent correlate of actigraphy-assessed sleep duration and efficiency and subjective sleep quality. These findings demonstrate the importance of considering novel social determinants that may underlie disparities in sleep health and considering policies to mitigate the root causes of sleep and other health disparities. Support (If Any): Funding was provided by the National Heart Lung Blood Institute ( R01 HL122460 and HL131531) and the National Cancer Institute (R01CA164137).